2005
DOI: 10.4049/jimmunol.174.8.5133-a
|View full text |Cite
|
Sign up to set email alerts
|

IL-2 Overcomes the Unresponsiveness but Fails to Reverse the Regulatory Function of Antigen-Induced T Regulatory Cells

Abstract: Inhibition of cytotoxicity by two different human A-LAK cell populations through F(abЈ) 2 of affinity-purified anti-laminin Ab. Sorted Leu-19 ϩ /CD3 Ϫ and Leu-19 ϩ /CD3 ϩ A-LAK cell populations were mixed with Cr-labeled target cells in the continued presence of 150 g/ml Ab for 4 h, and the resulting lytic activity was calculated as specified in Materials and Methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(33 citation statements)
references
References 0 publications
3
30
0
Order By: Relevance
“…We have found that antigen persistence can impair TCR signaling resulting in hyporesponsiveness (24). This hyporesponsiveness is gradually induced during antigen persistence with reduction of NFkB and AP1 activation (2, 24).…”
Section: Impaired Tcr Signaling During Chronic Virus Infectionmentioning
confidence: 99%
See 4 more Smart Citations
“…We have found that antigen persistence can impair TCR signaling resulting in hyporesponsiveness (24). This hyporesponsiveness is gradually induced during antigen persistence with reduction of NFkB and AP1 activation (2, 24).…”
Section: Impaired Tcr Signaling During Chronic Virus Infectionmentioning
confidence: 99%
“…This hyporesponsiveness is gradually induced during antigen persistence with reduction of NFkB and AP1 activation (2, 24). This characteristic phenotype of T-cell tolerance is similar to that observed in chronic HBV infection (25).…”
Section: Impaired Tcr Signaling During Chronic Virus Infectionmentioning
confidence: 99%
See 3 more Smart Citations